Agreement between supine and standing bioimpedance spectroscopy devices and dual‐energy X‐ray absorptiometry for body composition determination. (9th July 2019) - Esco, Michael R.; Fedewa, Michael V.; Freeborn, Todd J.; Moon, Jordan R.; Wingo, Jonathan E.; Cicone, Zack; Holmes, Clifton J.; Hornikel, Bjoern; Welborn, Bailey
Summary: Background: Research comparing bioimpedance spectroscopy (BIS) to dual‐energy X‐ray absorptiometry (DXA) is limited, especially with newer BIS devices that take measures in a standing position instead of the traditional supine position. Purpose: The purpose of this study was to compare a standing BIS device (BISSTA ) and a supine BIS device (BISSUP ) to DXA for measuring body fat percentage (BF%), fat mass (FM) and fat‐free mass (FFM) in a cohort of male and female subjects displaying a wide range of ages and BMI levels. Methods: Ninety‐five subjects (30 ± 15 years, 170 ± 8·0 cm, 72·6 ± 14·8 kg) participated in the study. Body composition measures were taken from BISSTA, BISSUP and DXA during a single visit to the laboratory following an 8‐ to 12‐h fast in a euhydration state. Results: Supine BIS device and BISSTA produced r ‐values >0·91 and low SEE values for all measurements compared to DXA. Effect sizes were 'trivial' for FFM comparing both BISSUP and BISSTA to DXA (<0·1) and 'small' for FM and BF% (<0·39). Compared to DXA, BISSTA resulted in lower total (TE) and constant errors/mean differences (CE) (TE < 3·6 kg, CE < −1·82 kg) versus BISSUP (TE < 4·35 kg, CE   <   −3·10 kg) for FFM. Conclusion: Fat‐free mass values for BISSTA resulted in the most comparable measurements to DXA with no mean differences and the lowest total error and effect size. However, the findings indicated both BIS devices may be acceptable alternatives to DXA for BF%, FM and FFM in clinical practice.